Improving Prosocial Ability in Early Age Children to Become A Personal who is Able to Adapt and Well Associalized - Daviq Chairilsyah (Pusat Penerbitan Universitas (P2U) Unisba, 2020)
The purpose of writing this article is to provide tips to teachers and parents in developing prosocial behavior, so that later children can socialize well in every line of life so that it will help shape children's positive personalities in adulthood. This article was written using the literature review method using various sources of articles and reading books. Teaching prosocial behavior to children can be done in an informal or formal way. The formal way is usually obtained when the child is in school and the teacher will be the mentor. Meanwhile, informal methods can be obtained from anywhere, from home and where the children play. Some ways that parents can do to teach children how to socialize, namely by making parents as role models, allowing children to express themselves, an open family atmosphere, activities in groups within the family, playing with family members, and motivating children by arousing feelings self-confident. Some of the ways that teachers can do are by providing various learning methods that make children active in social interaction with other children, become role models, motivate children to socialize in school and stimulate social learning settings in the classroom. AbstrakTujuan dari penulisan artikel ini adalah untuk memberikan tips kepada guru dan orang tua dalam mengembangkan perilaku prososial, agar nantinya anak dapat bersosialisasi dengan baik di setiap lini kehidupannya sehingga akan membantu membentuk kepribadian positif anak di masa dewasanya. Artikel ini ditulis menggunakan metode literatur reviu dengan menggunakan berbagai sumber artikel dan buku bacaan. Mengajarkan perilaku prososial pada anak dapat dilakukan dengan cara informal ataupun formal. Cara formal, biasanya diperoleh saat anak berada di sekolah dan guru yang akan menjadi pengarahnya. Sementara cara informal, dapat diperoleh dari mana saja, mulai dari rumah dan tempat anak bermain. Mengajarkan bersosialisasi sangat disarankan bagi orang tua dan guru di sekolah. Beberapa cara yang dapat dilakukan oleh orang tua untuk mengajarkan anak cara bersosialisasi yaitu dengan menjadikan orang tua sebagai role model, membiarkan anak berekspresi, suasana keluarga yang terbuka, beraktifitas dalam kelompok di dalam keluarga, bermain bersama anggota keluarga, dan memotivasi anak dengan cara membangkitkan rasa percaya dirinya. Beberapa cara yang dapat dilakukan guru adalah dengan memberikan berbagai metode pembelajaran yang membuat anak aktif dalam berinteraksi sosial dengan anak lain, menjadi role model, memotivasi anak untuk bersosialisasi di sekolah dan membuat stimulasi dalam seting belajar sosial di dalam kelas.